Avaliação dos Movimentos Periódicos das Patas na Síndrome das Pernas Inquietas, Utilizando um Modelo Animal Induzido pela Lesão do Núcleo Dopaminérgico A11 Com A 6-Hidroxidopamina - Lopes, Cleide [UNIFESP] (2011)
Background: Restless Legs Syndrome (RLS) is a major healthcare burden of increasing prevalence. It has been demonstrated that periodic limb movements in sleep (PLM) can occur as an isolated phenomenon, but they are often associated with RLS and represent the only symptom of this disorder that can be measured electrophysiologically. The aim of this study was to examine the sleep–wake behavior and the presence of PLM in a rat model of RLS induced by lesioning the A11 dopaminergic nuclei with the neurotoxin 6-hydroxydopamine (6-OHDA). Methods: Rats were implanted with electrodes for electrocorticography and electromyography. Sleep recordings were monitored during light and dark periods lasting 12 h each and were evaluated on days 7 (L7 group), 15 (L15 group) and 28 (L28 group) after injection of 6-OHDA or PBS (SHAM group). A control (CTRL) group that did not receive any injection was also included in the experiment. Wakefulness (WK) percentages were generated for 4-h segments of the dark period, yielding the following 3 bins: 7 to 11 pm, 11 pm to 3 am and 3 to 7 pm. Additionally, sleep efficiency, slow wave sleep, paradoxical sleep, WK, limb movements (LM) and PLM percentages were evaluated for the entire 12 h of the light and dark phases. Results: The results demonstrated that all the A11-lesioned rats exhibited an increased percentage of WK during the last block of the dark period, as would be expected for an animal model of RLS. In addition, at all time points after A11 lesioning, groups presented increased frequencies of LM and PLM most during light periods. Conclusions: Thus, this model has characteristics strikingly consistent with PLM in humans, including coexistence with RLS symptoms.